Agminated cellular blue naevi of the penis: dermoscopic, confocal and histopathological correlation of two cases. (23rd January 2016) - Collgros, H.; Vicente, A.; Díaz, A. M.; Rodríguez‐Carunchio, L.; Malvehy, J.; Puig, S.
Summary: Blue naevi may present rarely as multiple lesions grouped in a circumscribed area, described as agminated blue naevi. This clinical presentation may mimic metastatic malignant melanoma. We present two cases of agminated cellular blue naevi of the penis, with dermoscopy, reflectance confocal microscopy and histopathological correlation. Dermoscopy of the area showed multiple grouped lesions of homogeneous dark‐brown to blue colour. Using reflectance confocal microscopy, focusing on the bluish areas, predominantly bright dendritic cells were visible at the dermoepidermal junction and papillary dermis, while in the brownish areas the presence of dendritic and bright cells predominated in the basal layer. Our patients are of special interest as they are the first cases, to our knowledge, reported of agminated blue naevi on the penis, studied by both dermoscopy and confocal microscopy, confirming the diagnosis with histopathological correlation. Moreover, one case represented a divided or 'kissing' blue naevus of the penis.